Levels of childhood traumatic experiences and dissociative symptoms in extremely obese patients with and without binge eating disorder. (17th November 2019) - Belli, Hasan; Ural, Cenk; Akbudak, Mahir; Sagaltıcı, Eser
Abstract: Background: It has been suggested that obese patients with binge eating disorder (BED) show higher levels of dissociation and childhood trauma. Aim: This study assesses childhood trauma history and dissociative symptoms in obese patients with BED compared to obese patients without BED. Methods: The 241 patients participating in the study had to meet obesity criteria. These patients were applicants for bariatric surgery and were consulted by a psychiatry service. Patients were separated into two groups that were accompanied by BED diagnoses according to structured clinical interviews administered according to the DSM-IV (SCID-I). Patients were assessed using the Dissociation Questionnaire (DIS-Q) and the Childhood Trauma Questionnaire (CTQ). The two groups of patients were compared. Results: A total of 75 (31.1%) of the 241 obese patients were diagnosed with BED. The study showed that obese patients with BED had higher dissociative scores than those without BED ( p < .05). The results showed higher total scores and two different types of childhood trauma (physical abuse and emotional abuse) in BED patients compared to non-BED patients ( p < .05). Conclusions: Clinicians should be fully aware of BED, dissociative symptoms and childhood traumatic experiences. These results show that, for at least a sub-group of obese patients, BED is associated with obesity and may be connected with dissociative symptoms and childhood physical abuse and emotional abuse.